Production System Analysis of Brem Processing Unit (Case Study: The Industrial Centers of Brem in Kaliabu and Bancong Village, Madiun District) - Ardaneswari Dyah Pitaloka Citraresmi; Sri Kumalaningsih; Imam Santoso (Wacana Journal of Social and Humanity Studies, 2014)
The purpose of this study was to determine the condition, the priorities, and the strategy development policy of the brem Madiun production system as an effort to increase the brem Madiun production system. The samples which are used were the brem industries at industrial centers of brem in Kaliabu and Bancong Village at Madiun District. The main instrument to collect the data was a questionnaire for 21 respondents of business leaders. Data analysis method which is used was Analytical Hierarchy Process (AHP). The results showed that the sequence of factors causing the decline of brem’s production capacity were the final product (0,477), capital (0,244), raw materials (0,123), human resources (0,088), the tools and machinery (0,041), and the method (0,026). Benchmarks for goals to be achieved by the production system were the effectiveness of brem Madiun (0,548), productivity (0,227), efficiency (0,138), and quality (0,087). Strategies that can be done on developing the brem industry in Madiun are provision of venture capital to support the administrations, improvement of licensing services, improvement of joint venture accessibility on infrastructure production, supporting on marketing, improvement of human resources quality (coaching and training), development of product, improvement of business management, and development on network of business partnership respectively. After the several strategies development policy was formulated based on existing condition, then the performance of the brem Madiun production system can be improved. Keywords : Brem, Production System Analysis, Strategy Formulation